Influence Of Price And Product Variety Against Competitiveness (Survey Of Cahyati Fashion Indihiang Consumers, Tasikmalaya) - Yulianti; Askolani; Yusnita, Rita Tri (Journal of Management, Economic, and Accounting, 2023)
The purpose of this study was to determine the effect of price and product diversity on the competitiveness of Cahyati Fashion Indihiang, Tasikmalaya. The research method used is a quantitative method with a survey approach to 100 respondents who are consumers of Cahyati Fashion Indihiang, Tasikmalaya. The type of data used is primary data. The data analysis technique used is multiple regression analysis. The results of this test prove that price and product variety have a significant effect either partially or simultaneously on the competitiveness of Cahyati Fashion Indihiang, Tasikmalaya.